The Challenge of Metastatic Colorectal Cancer - Cidón, Esther Uña (Libertas Academica, 2010)
Colorectal cancer (CRC) is a very common disease with a high rate of mortality around the world, representing the second most frequent cause of cancer-related death. As the majority of patients are diagnosed with advanced cancer with a subsequent low five-year survival rate (10%), it is imperative to develop new strategies to treat this challenging patient population. Traditionally, patients received successive lines of chemotherapy and discontinued the treatment or switched to a different one in the event of disease progression. But despite the therapeutic advances achieved with combination chemotherapy regimens, particularly FOLFOX and FOLFIRI, considerable research has been necessary to further optimize chemotherapy for patients with metastatic colorectal cancer (mCRC). However, progress has been achieved over recent years. The most relevant relates to the approval of several new effective therapeutic drugs, such as monoclonal antibodies, which have greatly improved the outcomes for metastatic disease. The last agent approved has been panitumumab, which has been designed to target the epidermal growth factor receptor molecular pathway involved in the appearance and spread of cancer.